(untitled) (GnosisWisdom, 2023)
Knowing the learning styles of a human group with whom learning activities are going to be developed is a great success, hence the formulation of the problem of this research is: What relationship exists between learning styles and academic performance in the students of the first cycle of a private University of Sciences and Engineering? being the general objective: Establish the relationship that exists between learning styles and academic performance of students of the I cycle of a private University of Sciences and Engineering and the hypothesis: There is a direct relationship between learning styles and academic performance of those of the first cycle of a private University of Sciences and Engineering. The research was of a quantitative nature, basic type, correlational level and descriptive correlational design. The sample was taken in a probabilistic way made up of 200 students of the first cycle of a private University of Sciences and Engineering. Likewise, the technique of survey, filing and documentary analysis was used, the instruments being the inventory of Ralph's Learning Styles, bibliographic records and summary. The most important contribution of the present investigation considers that based on the data analyzed and processed, with a significance level of 5%, to test the hypothesis, the "t" test was performed for independent correlated samples, using the SPSS 26 program where it is determined that there is a significant correlation between the learning styles and the academic performance of the students of the first cycle of a Private University of Sciences and Engineering, making use of Pearson's "r" with a score of 0.523 and t=8.63 for related cases.